1993
DOI: 10.1246/cl.1993.481
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N-isopropylacrylamide) Microparticle Formation in Water by Infrared Laser-Induced Photo-Thermal Phase Transition

Abstract: Irradiation of a focused 1064 nm laser beam to an aqueous poly(N-isopropylacrylamide) solution resulted in the reversible microparticle (diameter ≈ 7 μm) formation through local heating of water by the laser beam and subsequent phase transition of the polymer solution. The microparticle produced was simultaneously manipulated in three-dimensional space by the incident 1064 nm laser beam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
69
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 7 publications
2
69
1
Order By: Relevance
“…[7][8][9][10][11] Among the various light sources, near-infrared (NIR) laser light is a fascinating stimulus especially from a biomedical point of view because biomedical tissues have a slight absorption in the NIR region, [12] which enables remote stimulation of the NIR absorbent in the body from the outside. Masuhara et al [10] described that strong NIR irradiation possesses potential applications for inducing a thermal phase transition through the photothermal conversion effect of H 2 O. Misawa et al [11] reported that the radiation forces generated by a strong focused IR laser beam (>1.2 W) could also induce a phase transition of a crosslinked PNIPAM gel. However, such a strong NIR-laser irradiation would cause damage to the tissue owing to the intense heating of water in the body through a photothermal effect.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] Among the various light sources, near-infrared (NIR) laser light is a fascinating stimulus especially from a biomedical point of view because biomedical tissues have a slight absorption in the NIR region, [12] which enables remote stimulation of the NIR absorbent in the body from the outside. Masuhara et al [10] described that strong NIR irradiation possesses potential applications for inducing a thermal phase transition through the photothermal conversion effect of H 2 O. Misawa et al [11] reported that the radiation forces generated by a strong focused IR laser beam (>1.2 W) could also induce a phase transition of a crosslinked PNIPAM gel. However, such a strong NIR-laser irradiation would cause damage to the tissue owing to the intense heating of water in the body through a photothermal effect.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] As an example, we previously reported that thermal phase separation of an aqueous triethylamine (TEA) solution was induced by the laser beam irradiated under an optical microscope, and a single micrometer-sized TEA droplet generated in the solution phase was trapped simultaneously by the incident laser beam. 4 Since water (H2O) absorbs incident 1064-nm laser light through the overtone band of the OH stretching vibration mode, this results in heat generation in the vicinity of the focal spot of the laser beam and, thereby, photothermal phase separation of an aqueous TEA solution.…”
Section: Introductionmentioning
confidence: 99%
“…This technique can also trap smaller nanoparticles such as polymer chains in aqueous solution [19]. Ishikawa et al first reported optical trapping of PNIPAM in an aqueous solution [20]. By the combination of radiation force and a photothermal effect, the technique can selectively trap a micro-assembly of polymer-rich domain at a focal point.…”
Section: Introductionmentioning
confidence: 99%